Carcass traits and meat quality of growing rabbits in pens with and without different multilevel platforms - M. Martino; S. Mattioli; P. Farkas; Zs. Szendrő; A. Dal Bosco; S. Ruggeri; Zs. Matics; C. Castellini; Zs. Gerencsér (World Rabbit Science, 2016)
The aim of this trial was to determine the effect of the presence of wire or plastic mesh elevated platforms on carcass traits and meat quality characteristics, with particular attention to the oxidative status of growing rabbits. A total of 174 five-week old rabbits were randomly divided into 3 groups with 2 replications (6 pens; 29 rabbits/pen): pens without platforms (NoP) with a stocking density of 16 rabbits/m2 and pens with wire-mesh platforms (WP) or plastic-mesh platforms (PP) that were placed on 2 levels, with a stocking density of 16 rabbits/m2 on the floor or 9.14 rabbits/m2 when the platform were included. At 84 d rabbits were slaughtered. The slaughter traits and Longissimus lumborum (LL) physical and chemical compositition were not affected by treatments. Rabbits from the PP group showed the highest retinol and γ-tocotrienol content on LL muscle, whereas the NoP ones showed a higher α-tocotrienol and α-tocopherol level. The absence of platforms led to decreased (P<0.001) thiobarbituric acid-reactive substances values and induced an improvement in n-3 polyunsaturated fatty acids. Levels of linoleic, linolenic and docosahexaenoic acids were equal to those of the WP group (23.45, 3.75, 0.64% in NoP and 22.6, 4.14, 0.53% in WP, respectively) but higher than in PP rabbits (20.86, 3.05, 0.45%, respectively). It can be concluded that the pens with elevated platforms provide greater possibilities for movement, which is beneficial from the viewpoint of animal welfare. However, this greater activity influences the oxidative status of the meat, decreasing the antioxidant content and worsening the lipid oxidation of rabbit meat.